2018
DOI: 10.3126/bjhs.v3i2.20938
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Study of Hysterectomy Specimens in Kathmandu Medical College Teaching Hospital

Abstract: Introduction: Uterus is subjected to many non-neoplastic and neoplastic diseases. Hysterectomy is the commonest gynecological surgery done for the management of the pathologies of the female reproductive system. Histopathological examination of hysterectomy specimens is done routinely which has both diagnostic and therapeutic significance.Objective: To study the common pathologies identified in hysterectomy specimens and to correlate them with the clinical findings.Methodology: A cross sectional study was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 3 publications
3
11
0
Order By: Relevance
“…In the myometrium, other pathologies included adenomyosis in 37 (23.57%) women and adenomyosis in combination with leiomyoma in 37 (23.57%) women. These findings are comparable to studies from Pakistan, India, and Nepal [20,23,25]. An Indian study has reported adenomyosis to be the dominant histopathological finding, followed by leiomyoma, with many cases also exhibiting dual pathologies [26].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the myometrium, other pathologies included adenomyosis in 37 (23.57%) women and adenomyosis in combination with leiomyoma in 37 (23.57%) women. These findings are comparable to studies from Pakistan, India, and Nepal [20,23,25]. An Indian study has reported adenomyosis to be the dominant histopathological finding, followed by leiomyoma, with many cases also exhibiting dual pathologies [26].…”
Section: Discussionsupporting
confidence: 85%
“…The mean age of women in the reproductive age group was 40.37 (± 5.47) years, whereas, most of the women belonged to the age range of 40-49 years. These findings are comparable to the average age of 41-50 years for women undergoing hysterectomies in developing countries [2,20]. However, as pathology reports were the only source of information and because of a wide standard deviation in the age of women, a bias of differential misclassification could not be excluded.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…16 Study done by Pradhan SB et al, reported; 60% incidence of leiomyoma and 14% incidence of adenomyosis. 15 Study by VV Sreedhar et al observed 20.5% metrorrhagia and post-menopausal bleeding in females. Increased risk of malignancy is associated with architectural complexity and cellular atypia.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the most common finding is leiomyoma. The leiomyoma incidence varies from 20.5% to 69% and the adenomyosis incidence varies from 7.5% to 47% in the 5,9,13,14,15 In a study done by Imam et al, incidence of leiomyoma was 29.04% while incidence of adenomyosis was 11.69%. 14 Study done by Baral R et al, revealed leiomyoma incidence as 48.6% and 10.3% incidence of adenomyosis.…”
Section: Discussionmentioning
confidence: 99%